Benzimidazole resistance in gastrointestinal nematodes of small ruminants of Uttarakhand - RIALCH, AJAYTA; VATSYA, STUTI; KUMAR, RAJEEV RANJAN (The Indian Journal of Animal Sciences, 2015)
The status of benzimidazole (BZ) resistance in gastrointestinal nematodes (GIN) was studied in a total of four flocks of sheep namely UTs1, UTs2, UTs3 (Uttarkashi district) and Bs1 (Bageshwar district) and four goat flocks namely UTg1, UTg2, (Uttarkashi district) and Bg1 (Bageshwar district) and Ug1 (U.S. Nagar district) of Uttarakhand state using egg hatch assay (EHA) and larval development assay (LDA). EHA detected resistance in two out of eight flocks (UTs3 and Ug1). Arithmetic mean and range of ED50 value of susceptible group was found to be 0.043μg/ml and 0.020-0.063μg/ml, respectively, and the same for resistant group were found to be 0.121μg/ml and 0.102-0.141μg/ml, respectively. The arithmetic mean and range of ED99 value of susceptible group was recorded as 0.295μg/ml and 0.170-0.500μg/ml, respectively, and that of resistant group was observed to be 2.970μg/ml and 1.794-4.146μg/ml, respectively. The arithmetic mean and range of LC50 value of susceptible group was found 0.003μg/ml and 0.002-0.003μg/ml, respectively, and those of resistant group was found 0.0150μg/ml and 0.010- 0.011μg/ml, respectively. While the arithmetic mean and range of LC99 value of susceptible group was found to be 0.010μg/ml and 0.007-0.011μg/ml, respectively and those of resistant group was observed to be 0.784μg/ml and 0.409-1.159μg/ml, respectively. Pooled coproculture examination revealed the presence of predominantly Haemonchus contortus, followed by Trichostrongylus spp., Oesophagostomum and Strongyloides, while infective larvae that survived in wells having higher concentrations of Thiabendazole were all Haemonchus with few Trichostrongylus. BZ resistance has not been reported earlier against Trichostrongylus spp. from Uttarakhand. For effective management of GIN in small ruminants, evaluation of efficacy of anthelmintics is important to regularly monitor anthelmintic resistance. The baseline information thus generated will enable timely management of benzimidazoles resistance in GIN.